Restoring or reinventing the virtuous cycle of crop-livestock integration? - Tarawali, Shirley A. (International Livestock Research Institute, 2021)
Shirley Tarawali, ILRI/GASL - ATF-EAAP LFS Commission one-day symposium 2021